On separatrix curves of a family of linear systems with pulse influence - Svistun, O. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For a family of linear systems of differential equations with pulse influence, we establish conditions of existence of separatrix curves and present a method for finding these curves.